One Mosque Five Pillars: Diversity of Preaching and Social Cohesion in Central Java - Lina Kushidayati; Moh Rosyid (Jurnal Dakwah Risalah, 2025)
This article explores social cohesion among Muslim groups in the village of Sragen, which is home to five distinct groups: NU, Muhammadiyah, MTA, LDII, and Salafi, as well as some individuals identified as abangan. Masjid Rohmat serves as the focal point for religious events, such as Eid al-Fitr and Eid al-Adha. This research is based on field research conducted in 2023. The data was then analyzed using a qualitative approach. This research has found, despite their differing interpretations and practices of faith, the residents of this village coexist peacefully and harmoniously. Key factors that contribute to this social cohesion include family ties and community activities. Many villagers share familial connections, even if they hold different religious affiliations. For instance, one mother regularly participates in Yaasin and tahlil gatherings, while her son is a member of LDII. In another household, the husband is affiliated with Muhammadiyah, while the wife attends MTA public congregations. Additionally, community members collaborate on various social activities, transcending their religious differences.